Not Going Gentle Into That Good Night: Science and Religion in the Face of Death - Code, Pamela (Journal of religion, spirituality & aging, 2015)
For millennia, religions have provided rituals bringing comfort in the face of death. Modern science, however, is developing new means for dealing with this phenomenon. Controversial issues include: how to ascertain death, particularly in light of premature burials; religious questions regarding the morality of embalming; religious questions regarding the desirability of burial versus cremation; and extending life in attempts to achieve immortalityversus the contention that mortality is the result of human sinfulness. This article explores these issues and seeks to answer the question of whether science has contributed positively or negatively to the experience of dying.